2016
DOI: 10.11646/phytotaxa.275.2.5
|View full text |Cite
|
Sign up to set email alerts
|

A new species of Youngia (Asteraceae, tribe Cichorieae) from Yunnan, China

Abstract: Youngia gongshanensis, a new species of Youngia sect. “Mesomeris” from Yunnan province of China is described and illustrated based on evidence from morphology and molecular phylogeny. The new species is superficially very similar to Y. atripappa having a solitary and erect stem and more or less lyrately pinnatisect leaves, but can be distinguished by capitula with 5–6 (vs. 12–15) florets, corolla tube glabrous (vs. sparsely pubescent with short white spreading hairs), pappus white (vs. grayish), bracts ovate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
2
5
0
Order By: Relevance
“…The examined micromorphological characters have provided diagnostic characters for taxonomic delineation of species in other Asteraceae taxa (Ayaz et al, 2019; Dere & Akcin, 2017; Karanović et al, 2015; Sonboli et al, 2013; Yuan, Bi, & Chen, 2015) and may be driven by differing ecological conditions (Haworth & McElwain, 2008). Our results confirmed that the pappus is directly joined to the pericarp in the investigated species, in agreement with other species in the genus (Ke & Chen, 2016; Peng et al, 2014; Figures 1j and 2j).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The examined micromorphological characters have provided diagnostic characters for taxonomic delineation of species in other Asteraceae taxa (Ayaz et al, 2019; Dere & Akcin, 2017; Karanović et al, 2015; Sonboli et al, 2013; Yuan, Bi, & Chen, 2015) and may be driven by differing ecological conditions (Haworth & McElwain, 2008). Our results confirmed that the pappus is directly joined to the pericarp in the investigated species, in agreement with other species in the genus (Ke & Chen, 2016; Peng et al, 2014; Figures 1j and 2j).…”
Section: Discussionsupporting
confidence: 91%
“…Scale bar = 5 μm. Arrows indicate nucleolar organizer regions (NORs) pericarp in the investigated species, in agreement with other species in the genus (Ke & Chen, 2016;Peng et al, 2014;Figures 1j and 2j).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Both cypselas and pollen material were collected from plants in the wild or from herbarium specimens. Sixty‐four samples were chosen for the molecular phylogenetics, representing the main clades of tribe Cichorieae resolved in published phylogenetic trees (Liu & al., 2013; Ke & Chen, 2016), and 20 samples representing 11 species of Dubyaea (Appendix 1). All voucher specimens were deposited in PE and IBSC.…”
Section: Methodsmentioning
confidence: 99%